Just culture : balancing safety and accountability - Dekker, Sidney (CRC Press, 2012)
A just culture protects people's honest mistakes from being seen as culpable. But what is an honest mistake, or rather, when is a mistake no longer honest? It is too simple to assert that there should be consequences for those who 'cross the line'. Lines don't just exist out there, ready to be crossed or obeyed. We - people - construct those lines; and we draw them differently all the time, depending on the language we use to describe the mistake, on hindsight, history, tradition, and a host of other factors. What matters is not where the line goes - but who gets to draw it. If we leave that t.